Factors associated with self-reported medical errors among undergraduate health science students in southern Ethiopia - Toitole, Kusse Koirita; Danaso, Fekade Tesfaye; Alto, Saron Assefa; Mohammed, Tofik; Dejene, Sisay; Boynito, Wanzahun Godana (Frontiers in Medicine, 2024)
Introduction: Medical errors are not uncommon, but they’re seldom reported. Patient safety practices are among the key areas for service improvement. This study aims to assess factors associated with self-reported medical errors among undergraduate health science students in southern Ethiopia. Methods: A facility-based cross-sectional study was conducted among health science students of Arba Minch University in 2018. The sample size was calculated using a single population proportion formula. A total of 287 Medical students who were fourth year and above, nursing and midwifery students who were second year and above, and other health science students who were third year and above were included. Results: The majority (82.1%) of the study participants had a ‘good’ knowledge score on patient safety. About 62.5% of the participants had a ‘favorable’ patient safety attitude. Only 38.6% of the study participants had ‘good’ patient safety practices. At adjusted analysis, participants who were doing their practical clinical attachment in the surgical and obstetric units were three times more likely to self-report medical errors as compared to those practicing in the pediatrics, internal medicine, and other units (AOR = 2.72, 95%CI: 1.16 – 6.39.97). Students who had not ever managed a patient independently were less likely to self-report medical error (AOR = 0.24, 95%CI: 0.08 – 0.72). The odds of self-reporting medical errors were less among participants who had not ever witnessed harm to patients by colleagues or other healthcare workers (AOR = 0.12, 95%CI: 0.05 – 0.29) and participants who had not ever witnessed harm to a close friend or family member (AOR = 0.36, 95%CI: 0.16 – 0.80). Conclusion: One in five of the participants reported having harmed patients while practicing. Only 38.6% of the study participants had good patient safety practices. Having worked in surgical and obstetrics units, having managed a patient independently, and having witnessed harm to a patient were associated with self-reporting of medical errors.